Representações sociodiscursivas de imigrantes e refugiados no cenário brasileiro contemporâneo - Bárbara Mano de Faria (2020)
This paper studies socio-discursive representations of immigrants and refugees in the Brazilian contemporary context, resorting to the French theory of Discourse Analysis (DA) and some related theories/disciplines. The contemporary migration phenomenon, marked by many modalities of displacement and by increasingly bigger human flows, has reached significant projections in institutional discourse in Brazil and in the world. Focusing on the so-called “South-South migrations”, these discourses tend to represent migration according to the imaginary of an international crisis, so as to justify migratory policies based on border closure and social marginalization of immigrants and refugees. Besides, there are few spaces for the members of these groups to talk about themselves and their migratory conditions, so that their sociodiscursive representations, which are, generally, presented by the media, could reverberate in the public opinion and influence/reflect the common sense (doxa). Thus, in order to receive these individuals in the country in a humanitarian way, it is fundamental to understand how the status attributed to them influences the social and political treatment they are given. In this way, we seek to analyse the socio-discursive representations which emerge in the media instance and compare them to the way in which immigrants and refugees represent their own life stories. Based on a corpus composed by pieces of news from the reference press of Minas Gerais and by life stories obtained in interviews given by immigrants and refugees who live in the Great Belo Horizonte, we, firstly, presented an overview of the main national and international agreement policies and documents, which define, in a legal way, the many categories of migrants, and discussed their representation in these instruments. Secondly, we presented the notions of social representations and of socio-discursive imaginaries, which are the basis of this study; some theoretical approaches which deal with media discourses and with public opinion; as well as Sociology and DA references to the concept of life stories. We also resorted to theoretical and methodological literature to build an “individualized” device of analysis, in light of Global Semantics. Finally, we described the methodological procedure adopted to collect, register and analyse the texts that compose our corpus, highlighting the qualitative nature of this study. After analysing the media texts, grouped by thematic axes, and the life stories, which were examined separately, we could confirm our initial hypotheses, especially the fact that there is an uneven distribution of speech spaces dealing with contemporary migrations, which favors certain politically and socially intitutionalized discourses and inhibits, or even silences, the voice(s) of immigrants and refugees, who do not feel, in most cases, represented by institutional/media discourses.